2010
DOI: 10.1167/10.5.5
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the mechanisms that may underlie the reduction in contrast sensitivity during dynamic accommodation

Abstract: Head and eye movements, together with ocular accommodation enable us to explore our visual environment. The stability of this environment is maintained during saccadic and vergence eye movements due to reduced contrast sensitivity to low spatial frequency information. Our recent work has revealed a new type of selective reduction of contrast sensitivity to high spatial frequency patterns during the fast phase of dynamic accommodation responses compared with steady-state accommodation. Here were report data whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…When the target is blurred substantially (≥1.5D), only low SF information will be available to the accommodation control system, as these SFs are less affected by blur 44 . More recent work has suggested that the role of high SF information is limited to final response refinement as high SF information is unlikely to be perceived during the step response 31,45 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When the target is blurred substantially (≥1.5D), only low SF information will be available to the accommodation control system, as these SFs are less affected by blur 44 . More recent work has suggested that the role of high SF information is limited to final response refinement as high SF information is unlikely to be perceived during the step response 31,45 …”
Section: Discussionmentioning
confidence: 99%
“…44 More recent work has suggested that the role of high SF information is limited to final response refinement as high SF information is unlikely to be perceived during the step response. 31,45 The use of continuous negative feedback control to maintain an accurate accommodation response level is well established. Our results show that for small changes in accommodation stimulus level, target SF has considerably less effect upon the magnitude of the response, as the system can obtain accurate focusing information from all targets, irrespective of SF.…”
Section: Discussionmentioning
confidence: 99%
“…Our results are consistent with those from previous studies. To illustrate, Muck (Mucke et al, 2010) reported that dynamic accommodation is related with contrast sensitivity at high spatial frequency. The faster the dynamic response, the more reduced the contrast sensitivity for high but not low spatial frequency (Mucke et al, 2010).…”
Section: Correlations Among Accommodative Facility Vergence Facility and Contrast Sensitivitymentioning
confidence: 99%
“…To illustrate, Muck (Mucke et al, 2010) reported that dynamic accommodation is related with contrast sensitivity at high spatial frequency. The faster the dynamic response, the more reduced the contrast sensitivity for high but not low spatial frequency (Mucke et al, 2010). To perform well in an accommodative facility test, individuals should have a good contrast sensitivity for high spatial frequency.…”
Section: Correlations Among Accommodative Facility Vergence Facility and Contrast Sensitivitymentioning
confidence: 99%
“…This is expected since it is understood that the accommodation controller initially uses low spatial frequency information within a target to initiate a step response, which is then further refined using high spatial frequency information, which becomes increasingly available as the target becomes less blurred. [76][77][78][79] The vast majority of slow drift was in the correct direction, as shown by the example trace in Figure 8. This was not influenced by CL type, again suggesting that this is a normal AR as opposed to a feature of MFCL viewing.…”
Section: Step Responses and CL Typesmentioning
confidence: 86%